2020
DOI: 10.1111/os.12651
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Anatomical Repair of Anterior Talofibular Ligament for Chronic Lateral Instability of the Ankle: Medium‐ and Long‐Term Functional Follow‐Up

Abstract: Objective: To evaluate the functional outcomes of arthroscopic anatomical repair of anterior talofibular ligament (ATFL) in the treatment of chronic lateral ankle instability (CLAI) during medium-and long-term follow-up.Methods: From September 2014 to August 2017, the data of 37 patients (23 males, 14 females; 12 left ankles, 25 right ankles) aged between 21 and 56 years, with an average age of 32.17 AE 6.35 years, presenting with CLAI, was retrospectively analyzed. Among them, 32 injuries were caused by sprai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Pain levels at final evaluation, measured by the VAS, were found similar to the work of Feng et al 12,13 (1.12 + 0.13), which assessed this outcome in patients who underwent a Brostrom arthroscopic repair at medium-term follow-up. Findings of the current study support ankle arthroscopic ligament repairs, specifically when combining lateral and medial complexes, as a secure option in terms of reestablishing a painful joint.…”
Section: Discussionsupporting
confidence: 78%
“…Pain levels at final evaluation, measured by the VAS, were found similar to the work of Feng et al 12,13 (1.12 + 0.13), which assessed this outcome in patients who underwent a Brostrom arthroscopic repair at medium-term follow-up. Findings of the current study support ankle arthroscopic ligament repairs, specifically when combining lateral and medial complexes, as a secure option in terms of reestablishing a painful joint.…”
Section: Discussionsupporting
confidence: 78%
“…There were 3 studies included in the AOFAS score analysis, with 136 males and 84 females (Figure 3). 6,7,16 There was no significant difference in AOFAS scores between males and females (90.44 ± 4.82 for males, 90.19 ± 3.54 for females, P = .1586).…”
Section: Functional Outcomesmentioning
confidence: 81%
“…Among the 7 studies, 618 patients underwent anatomic primary lateral ankle ligament repair. Xu et al 16 reported sex-specific outcomes as the primary study outcome, while Hu et al, 10 Lee et al, 11 Corte-Real and Moreira, 6 Park et al, 13 Xu and Lee, 17 and Feng et al 7 reported sex-specific outcomes as secondary study outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…This approach is safe, and allows predictable return to preinjury daily and sport activities in most patients, but prospective RCTs are needed. 71 Indeed, recent studies 34,94 reported better clinical outcomes of arthroscopic than open technique at a midterm follow-up (26.1 ± 13.3 months and 12 months, respectively), with significantly less perioperative pain, higher AOFAS scores after 6 months of follow-up, and with no complications.…”
Section: The Role Of Arthroscopymentioning
confidence: 98%